Pulmonary innate lymphoid cell responses during rhinovirus-induced asthma exacerbations - Dhariwal,J; Cameron,A; Wong,E; Trujillo-Torralbo,B; Del,Rosario A; Bakhsoliani,E; Paulsen,M; Jackson,D; Hansel,TT; Edwards,M; Cousins,D; Walton,RP; et al. (Journal of Allergy and Clinical Immunology, 2021)
Rationale Type 2 innate lymphoid cells (ILC2s) are significant sources of type 2 cytokines, which are implicated in the pathogenesis of asthma and asthma exacerbations. The role of ILC2s in virus-induced asthma exacerbations is not well-characterized. Objectives To characterize pulmonary ILC responses following experimental rhinovirus challenge in patients with moderate asthma and healthy subjects. Methods Patients with moderate asthma and healthy subjects were inoculated with rhinovirus-16, and underwent bronchoscopy at baseline, day 3 and day 8 post-inoculation. Pulmonary ILC1s and ILC2s were quantified in bronchoalveolar lavage (BAL) using flow cytometry. The ratio of BAL ILC2:ILC1 was assessed to determine their relative contributions to the clinical and immune response to rhinovirus challenge. Measurements and Main Results At baseline, ILC2s were significantly higher in patients with asthma than healthy subjects. At day 8, ILC2s significantly increased from baseline in both groups, which was significantly higher in asthma than in healthy subjects (all comparisons P<0.05). In healthy subjects, ILC1s increased from baseline at day 3 (P=0.001), while in patients with asthma, ILC1s increased from baseline at day 8 (P=0.042). Patients with asthma had significantly higher ILC2:ILC1 ratios at baseline (P=0.024) and day 8 (P=0.005). Increased ILC2:ILC1 ratio in asthma correlated with clinical exacerbation severity and type 2 cytokines in nasal mucosal lining fluid. Conclusions An ILC2-predominant inflammatory profile in asthma was associated with increased severity and duration of rhinovirus infection compared with healthy subjects, supporting the potential role of ILC2s in the pathogenesis of virus-induced asthma exacerbations. Clinical trial registration available at www.clinicaltrials.gov, ID: NCT01773590